Effect of Grain and Calcinations Kaolin Additives on Some Mechanical and Physical properties on Low Density Polyethylene Composites - Shnean, Zanaib Y. (Al-Khwarizmi Engineering Journal, 2019)
In this work, a composite material was prepared from Low-density polyethylene (LDPE) with different weight percent of grain and calcinations kaolin at temperature of (850oC) using single screw extruder and a mixing machine operated at a temperature between (190-200oC). Some of mechanical and physical properties such as tensile strength, tensile strength at break, Young modulus, and elongation at break, shore hardness and water absorption were determined at different weight fraction of filler (0, 2, 7, 10 and 15%). It was found that the addition of filler increases the modulus of elasticity, elongation at break, shore hardness and impact strength; on other hand, it decreases the tensile strength and tensile strength at a break. Absorption test was carried out in water at different immersion times and different composite .The results of absorption show that it obeys Fick’s law and after the addition of kaolin the amount of absorption decrease. Calcinations kaolin filler produces better mechanical properties , than grain kaolin fillers.